Analisis Forensik Cyberbullying pada Aplikasi IMO Messenger Menggunakan Metode Association of Chief Police Officers - Imam Riadi; Sunardi Sunardi; Yana Safitri (Jurnal Bumigora Information Technology (BITe), 2023)
The development of computer technology is increasing very rapidly. This has both positive and negative impacts. One of the negative impact is committing acts of cyberbullying. This study uses the ACPO method to investigate the cyberbullying crimes through evidence that will be found. The ACPO method in the Imo Messenger investigation has four stages, namely Plan, Capture, Analysis, and Present. Digital data in the form of 16 conversation text, 29 user ID, 6 deleted data, and a group used as parameters in the research process. The test was performed using the tool of MOBILEdit Forensic Express. The results based on the digital data obtained 100% of conversation text, user ID, and group, while 0% for deleted data.